Written Corrective Feedback on Intermediate EFL Learners’ Formulaic Errors: The Impact of a Teacher Awareness-Raising Program - Servat Shirkhani; Samaneh Omidi (Journal of Modern Research in English Language Studies)
Written corrective feedback has been extensively investigated with regard to its effectiveness, comparison of its different types, and perceptions about its effectiveness. However, few studies have addressed the types of errors receiving Corrective Feedback (CF) and still, much fewer have focused on formulaic errors as targets of CF. Thus, the current study compared formulaic and non-formulaic errors as targets of CF in learner writing. In addition, it examined the CF types provided for these errors. Finally, it sought the effect of a teacher awareness-raising program on teachers’ attention to formulaic versus non-formulaic errors and on the CF types used to correct these errors. To achieve these purposes, eight English language teachers from four language institutes were selected through convenience sampling. First, during two sessions, the teachers asked the learners to write two compositions on two writing topics. Next, an awareness-raising program for teachers was run to raise the teacher’s awareness level about formulaic and non-formulaic errors and CF types for correcting such errors. Then, the learners were asked to write two other compositions each in one session. The results showed that before the treatment, non-formulaic errors received considerably more CF than formulaic errors and that the percentage of direct CF was more than other CF types. In addition, the study showed that the awareness-raising program for teachers influenced their attention to formulaic errors. The findings of this study indicate that teachers need awareness-raising about the importance of formulaic sequences and the need to correct formulaic errors whenever possible.